Reflections on Information Reception and Feedback in Patients Embodied Cognition: Taking Patients Undergoing Cataract Surgery as An Example - Jingjing WANG; Honglin LUO; Xia LI (Yixue yu zhexue)
Patients embodied cognition refers to the cognitive activities of patients' body during illness, within clinical settings, and throughout the progression of disease. The treatment experience of patients is not merely an information-receiving and feedback process, but rather a dynamic interplay among sensory perception, emotional cognition, and social context. In terms of information reception, vision dominates the perception reconstruction throughout the surgical process, and hearing assists in cognitive adjustment to compensate for the information gap during the visual adaptation period. In terms of information feedback, the mind integrates sensory input to drive behavioral adaptation, and language expression becomes the key medium for doctor-patient communication and experience externalization. Medicine should go beyond the assessment of simple biological indicators and incorporate patients' sensory-cognitive-language feedback into the therapeutic framework. This not only provides new ideas for treatment and rehabilitation but also expands the philosophical and ethical dimensions for the application of embodied cognition theory in medical practice.